Village Street Lighting with Solar Cells and Counseling on Electricity & EBT for the Cikembang Caringin Community, Sukabumi Regency - Marina Artiyasa; Anggy Pradifth; Muchtar Setyo Ali Yudono; Aryo de Wibowo; Isep Tedi (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2023)
Street lighting is an important aspect in the lives of rural communities. However, the Cikembang Caringin area in Sukabumi Regency still faces challenges in providing efficient and sustainable street lighting. To overcome this problem, this study was carried out with the aim of implementing solar cells as an alternative source of street lighting and providing education about electricity to the local community. The results of this study show that the implementation of solar cells as a source of street lighting in Cikembang Caringin provides positive results. Street lighting produced from a solar cell system is able to provide sufficient light for the community at night, thereby providing a sense of security and comfort for local residents.The education about electricity, namely the dangers of short circuits and also about Renewable Energy provided by Pak Anang and Pak Tyo, had a positive impact in increasing public awareness of the wise and sustainable use of energy. It is hoped that the findings from this research can be an inspiration for the development of renewable energy-based street lighting in other rural areas.